2017
DOI: 10.1007/s00049-017-0239-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the preen wax composition of the Herring gull Larus argentatus

Abstract: The preen gland produces oily secretion, which smeared onto a bird’s plumage improves its maintenance. The main components of the secretion are waxes, and its composition often changes during the year. The aim of this study was to determine the differences in the chemical composition of preen waxes in adult herring gulls Larus argentatus, captured in Poland in winter and in the breeding season. Preen gland secretions of herring gulls consist of monoester waxes, composed of about 29 saturated C7–C16 fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…However, neither feather sample produced ToF-SIMS spectra that in detail mimic the keratin spectrum, indicating that other molecular components may also be contributing to the spectra. This difference can be explained for the control feather in part by the presence on the feather surface of not only keratin but also of preen waxes, which are used by birds to protect their feathers from environmental influences [5254]. These waxes are identified in the negative ion spectra as monoester molecular ions in the mass range m/z 290–460 and diester molecular ions at m/z 680–800 (S3 Fig), corresponding to the main components of bird feather preen waxes [52].…”
Section: Resultsmentioning
confidence: 99%
“…However, neither feather sample produced ToF-SIMS spectra that in detail mimic the keratin spectrum, indicating that other molecular components may also be contributing to the spectra. This difference can be explained for the control feather in part by the presence on the feather surface of not only keratin but also of preen waxes, which are used by birds to protect their feathers from environmental influences [5254]. These waxes are identified in the negative ion spectra as monoester molecular ions in the mass range m/z 290–460 and diester molecular ions at m/z 680–800 (S3 Fig), corresponding to the main components of bird feather preen waxes [52].…”
Section: Resultsmentioning
confidence: 99%
“…We found that preen oil composition differs between sexes only in the non-breeding season, with males having higher abundance of one sterol and of a few ketonic compounds compared to females. In several bird species, preen oil composition varies with sex in the breeding season (Whittaker et al 2010, Leclaire et al 2011, Amo et al 2012, Jacob et al 2014, Fischer et al 2017. In many vertebrates, sex-differences in chemical profiles are mediated by steroid hormones (Wyatt 2014), for which sex variations are often higher during the breeding season (Wingfield et al 1990).…”
Section: Sex But No Age Differences In Chemical Profilesmentioning
confidence: 99%
“…Thus, gerygones might also prevent predation by rodents due to lack of odour cues. This has been observed in other bird species that are able to reduce their own smell by changing the composition of preen wax during the breeding season (Kolattukudy et al , Reneerkens et al , Soini et al , Fischer et al ). However, it is also possible that fan‐tailed gerygone already had a naturally low vulnerability to predation by rats, for example due to low odour production or little accessible nest locations, even if these placements are conspicuous (Dennison et al , Noske ).…”
Section: Discussionmentioning
confidence: 60%